Сучасні принципи міжнародного права в ієрархії норм міжнародного, наднаціонального і національного права - Задорожна, Світлана (Правові горизонти. Суми, 2019)
The development and evolution of the legal regulation of relations of an international legal nature requires a rethinking of the meaning and place of the basic norms of the principles of international law in it. The emergence of a new supranational level of regulation of such relations requires answers about the change or consolidation of the fundamental role in such regulation of the generally accepted principles of international law. The place of the principles of modern international law in the hierarchy of the norms of national law is considered within the framework of the problem of the correlation of sources of international law and internal law. Unity in the solution of this issue in the doctrine of both national and international law has not been achieved. Thus, this problem under consideration is part of the problem of the interaction of national legal systems and international law with comments on the specifics of the norms and principles of international law. The question of the place of the principles of modern international law in the hierarchy of the norms of national law can only be concluded that it is based on the general tendency in the world characterized by "friendly attitude" to the generally accepted principles of international law, recognition of the nature of their priority rules in relation to national law, simplified implementation mechanism. And although the ratio of universally accepted principles and constitutions of states does not always reinforce the preference of the former, the content of the constitutions of most states and national practice, as a rule, confirms their supremacy at the national legal level. The lack of unity in the solution of this issue makes it necessary to seek a solution to the question of the place of the principles of modern international law in the hierarchy of norms in international law. An essential feature of the principles of international law is their normativity, they regulate international legal relations, both directly and with the help of specific norms. Principles are primitive, since they determine the content and purpose of the norms of international law, and determine the structure of international law as a whole, and harmonize the rules that are included therein. Such a supranational action serves as an additional guarantee of consolidation of the principles and the possible filling of gaps in national legal systems where there is no recognition of the principles of international law at the constitutional level. Moreover, given the recognition of the general principles of international law in the EU law as the basic standards for the functioning of the EU as a whole and respect for the principles of international law in the regulation of similar relations at the supranational level, they indicate their special place and priority in the EU legal system.